2020
DOI: 10.1080/17512786.2020.1776142
|View full text |Cite
|
Sign up to set email alerts
|

“Going Offline”: Social Media, Source Verification, and Chinese Investigative Journalism During “Information Overload”

Abstract: Based on interviews with 25 investigative journalists in Beijing, China, this study suggests digital journalists may be increasingly challenged by a sense of "information overload" as they navigate social media and online environments crowded with dis-and mis-information, fake profiles and sources, and massive amounts of opinion journalism that is presented as professional journalism. This overload has reinforced Chinese investigative journalists' dedication to a conventional form of verification: meeting face… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 61 publications
0
4
0
1
Order By: Relevance
“…physicians say that COVID-19 vaccines are safe) (e.g. [68] , [69] ). In our results instead, we found that the medical source is effective when used to endorse a belief (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…physicians say that COVID-19 vaccines are safe) (e.g. [68] , [69] ). In our results instead, we found that the medical source is effective when used to endorse a belief (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…According to de Haan et al (2022); explicitly designed algorithmic tools for journalistic research are rarely or never used. Xu and Gutsche (2021) confirm in their study that Chinese journalists still use offline tools for reviewing and sourcing information, while Western journalists have turned to digital and online tools. Therefore, tools developed for journalists' fact-checking must be simple and integrated into newsrooms' editorial systems to ensure effective news production.…”
Section: Verification Practices and Technologymentioning
confidence: 74%
“…In a contrary study by Zhang (2020), journalists believe that social media is a reliable news source, and the more one uses social media to verify facts, the less likely one is to cross-check them with interviews. Supported by Xu and Gutsche (2021), "information overload" clarifies that these journalists are neither unable nor unwilling to verify online material due to "overload". Therefore, several journalists have been charged with spreading Fake News.…”
Section: Social Media Use and Fake Newsmentioning
confidence: 99%
“…At the same time, AI enables also the possibility to detect disinformation (Kaplan, 2020), when the process is guided by professionals. This feature can be very interesting in a country like China, where rumours are forbidden in media (Guo, 2020), and individual fact-checking requires a heavy investment of time (Xu & Gutsche, 2021), or it is not commonly performed (Wang et al, 2022), due to the link between media and political institutions and leaders. To do this, we agree with Xi & Latif (2022) that a "double gatekeeping" (p. 41) is needed, the first gatekeeping should be performed from the machine, to the sources; and the second one should be completed from a professional to the machine results.…”
Section: Discussionmentioning
confidence: 99%